Analisis Yuridis Terhadap Tindak Pidana Penipuan (Qawanin Jurnal Ilmu Hukum, 2021)
AbstractThis study aims to identify and analyze legal material, to analyze judges&; legal considerations in makingdecisions on the criminal act of fraud. This research uses a normative research method, with the coverage of primary, secondary and tertiary legal materials, this research was conducted at the Makassar District Court, with the legal material obtained will be analyzed using a statutory approach to obtain a systematic picture., with the legal materials obtained and analyzed using astatutory approach to obtain a systematic picture. The results of this study indicate that the application of criminal law and criminal sanctions against fraud cases No.1609 / Pid.B / 2020 / PN MKS is in accordance with applicable legal norms, all elements of criminal acts regulated in article 378 of the Criminal Code have all been fulfilled where the defendant was charged.sentence of 1 (one) year and 3 (three) months imprisonment. Research recommendations If this policy is seen as a strategy to reduce crime in prisons, then the government deserves to enforce the law against riminals.AbstrakPenelitian ini bertujuan untuk mengidentifikasi dan menganalisis materi hukum, menganalisis pertimbangan hukum hakim dalam mengambil keputusan atas tindak pidana kecurangan. Penelitian ini menggunakan metode penelitian normatif, dengan cakupan bahan hukum primer, sekunder dan tersier, peneleitian ini dilakukan di Pengadilan Negeri Makassar, dengan bahan hukum yang diperoleh akan dianalisismenggunakan pendekatan perundang-undangan untuk memperoleh gambaran yang sistematis. Hasil penelitian ini menunjukkan penerapanhukum pidana dan sanksi pidana terhadap kasus penipuan No.1609/Pid.B/2020/PN MKS sudah sesuai dengan norma hukum yang berlaku, semua unsur tindak pidana yang diatur dalam pasal 378 KUHP semua telah terpenuhi yang mana terdakwa dijatuhi hukuman 1(satu) tahundan 3(tiga) bulan penjara. Rekomendasi penelitian Jika kebijakan ini dilihat sebagai salah satu strategi untuk mengurangi tindak kejahatan di Lembaga pemasyarakatan, maka pemerintah pantas untuk menegakkan hukum terhadap pelaku kejahatan.